The Difficulties of Differential Diagnosis of the Bronchial Obstruction Syndrome - I. V. Demko; M. G. Mamaeva; A. Yu. Kraposhina; E. A. Sobko; N. V. Gordeeva; S. A. Sidorov; V. V. Dyatlovskij (Архивъ внутренней медицины)
Bronchial obstructive syndrome is a violation of bronchial patency of functional or organic origin, which is manifested by shortness of breath, suffocation attacks, cough, tachycardia. The most common cause of bronchial obstructive syndrome is chronic obstructive pulmonary disease and bronchial asthma. In some cases, the cause of bronchial obstruction is tumors or tumor metastases to the lungs. The article describes a clinical case of bronchial obstructive syndrome, showing that all patients with bronchial asthma, in the absence of an effect from the prescribed adequate basic therapy, with no control over the disease, should be well examined for an alternative diagnosis. In our case, a thorough examination of the patient allowed the allergist to diagnose central lung cancer with metastases to the lymph nodes of the mediastinum. A feature of the case is the primary resistance to tyrosine kinase inhibitors, revealed during a genetic study, which determined the scheme of further polychemotherapy. This clinical case proves the need for differential diagnosis, with a comprehensive approach and the use of various examination methods.